A linguistic and non-linguistic analysis of gender differece in writing style inadolescent blogs - Hii, Angeline Hui Wen (University Malaysia Sarawak, UNIMAS., 2009)
This study examines gender variation on writing style employed by adolescent male and female blog writers (13 – 22 years of age), who create and maintain blogs made publicly accessible on the Internet. The objectives of the study were to find out the linguistic and non-linguistic features employed when writing blogs so as to determine the extent to which these writing styles were similar linguistically and nonlinguistically in line with the checklist adapted from various findings and claims. 40 personal blogs, with five up-to-date entries were selected using the stratified random sampling method with equal number of male- and female- authored blogs. The online identify was gathered from the explicit display of demographic information. Data were analysed and checked against the above checklist to discover possible gender variation in writing. The blog analysis was done at word and sentence level. Overall, presentation of the results and findings showed that the features employed reflected the criteria in the adapted checklist in great similarities with notable difference in the low occurrence of taq questions across all gender. It was also noted that female blog writers showed greater consistency in the use of blogwords in their writing. Besides, the non-linguistic features also showed a high degree of resemblance to the adapted checklist with the significant difference that the spacing element was not applicable at any point in the blog samples studied. The study also discovered that textual emoticons were used more frequently as compared to graphical icons. All these findings confirmed with the literature reviewed that female writing were more ‘interactional’ with personalization of texts and male writing were more ‘informational’ with specification of things and concepts (Biber, 1995 cited in Argamon et al., 2003). As a whole, a close examination of blog analysis categorized the patterns into male preferential features and female preferential features, suggesting possible gender markers of the language. In particular, personal pronouns, intensifier, taq question, blogwords, emoticons and paralanguage were related to female writing whereas preposition, determiner, quantifier and hyperlinks were closely associated with male writing. Contrary to prediction, the results indicated that male blog writers tended to use more modal auxiliary words, which was fairly justifiable according to Saal (2005) to establish a close writer-reader relationship. All in all, the linguistic and non-linguistic features as in the present study demonstrated gender-specific capabilities and might be further replicated to determine the relationship of gender and language use in other contexts of study.